Use of H1N1 strain A/PR/8/34 influenza to build a mouse model of viral respiratory sepsis - Yaqing Jiao; Yuee Cai; Yilin Zhang; Ka-Tim Choy; Ka-Man Cheng; John M. Nicholls; Pui-Kin Lam; Hui-Ling Yen; Timothy H. Rainer (Laboratory Animal Research)
Abstract Background Community-acquired respiratory infections are a prevalent cause of sepsis. Current animal models simulate peritoneal rather than respiratory sepsis. This study sought to appraise an influenza model for its ability to develop sepsis. Methods Twenty-four six-week-old male BALB/c mice were intranasally inoculated with H1N1 strain A/PR/8/34 virus at 3.7 × 10− 1, 3.7 × 100, 3.7 × 101, 3.7 × 102, 3.7 × 103, 3.7 × 104 median tissue culture infectious dose (TCID50) to acquire different levels of clinical severity. Murine Sepsis Score (MSS) was recorded daily over 14 days. Platelets, serum bilirubin and creatinine levels were measured to reflect coagulopathy, liver and renal dysfunction. These three parameters are from the Sequential Organ Failure Assessment (SOFA) score which is routinely used for monitoring human sepsis. The primary outcome is organ dysfunction. Results Out of 24 infected mice, seven (29%) did not survive beyond 9 days. MSS predicted mortality with an AUC of 0.989 (95%CI: 0.978-1.000; P < 0.001). Liver and renal dysfunction were detected in one non-survived and six survived mice. Histological examination revealed inflammation in lung and liver but not kidney tissues. Conclusions This study demonstrates the potential of influenza to cause organ dysfunction, providing a basis for building a murine model specific for viral respiratory sepsis, and more closely simulating human viral sepsis.